2019
DOI: 10.1089/end.2019.0018
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Obesity in Patients Undergoing Robotic Partial Nephrectomy

Abstract: Introduction: As the prevalence of obesity increases worldwide, an increasing proportion of surgical candidates have an elevated body mass index (BMI), with associated metabolic syndrome. Yet there exists limited evidence regarding the effect of elevated BMI on surgical outcomes in robotic surgeries. We examined whether obese patients had worse perioperative outcomes and postoperative renal function after robotic partial nephrectomies (RPNs). Materials and Methods: We performed a multi-institutional analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
(30 reference statements)
3
4
0
Order By: Relevance
“…Our findings on impacts of obesity on EBL and length of hospital stay were consistent with literature showing that obesity increases blood loss during partial nephrectomy but no effect on length of hospital stay ( 16 - 20 ). However, unlike our study, previous studies focused on evaluating safety of minimally invasive surgical approach (laparoscopic or robotic partial nephrectomy) among obese patients and found no association between obesity and warm ischemia time ( 18 - 20 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings on impacts of obesity on EBL and length of hospital stay were consistent with literature showing that obesity increases blood loss during partial nephrectomy but no effect on length of hospital stay ( 16 - 20 ). However, unlike our study, previous studies focused on evaluating safety of minimally invasive surgical approach (laparoscopic or robotic partial nephrectomy) among obese patients and found no association between obesity and warm ischemia time ( 18 - 20 ).…”
Section: Discussionsupporting
confidence: 91%
“…Obesity and metabolic disorders, however, may complicate the surgical procedure leading to poor perioperative outcomes. In particular, prior studies of partial nephrectomy have shown that obesity increase ischemia time ( 16 ), estimated blood loss (EBL) ( 16 - 19 ), acute kidney injury ( 20 ), and rate of conversion to open surgery ( 21 ). Studies in patients who underwent laparoscopic radical nephrectomy have also shown that obesity increases operative time ( 22 ), rate of conversion to open surgery ( 23 ), and length of hospital stay ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our finding is similar to other studies consisting of gastroenterological cancer surgery, colorectal cancer surgery, and liver surgery, in which they have also shown that obesity prolongs operative time [23]. This is likely a result of thicker abdominal walls and perinephric fat, which result in slower dissection and poses unique intraoperative challenges [24,25]. However, the clinical significance of a mean difference of 22 min may be questionable.…”
Section: Discussionsupporting
confidence: 88%
“…Results of multivariable analysis show that obesity (OR = 1.81; p = 0.031), male sex (OR = 1.54; p = 0.028), and larger tumor size (OR = 1.23; p < 0.001) were associated with a significant increase in the likelihood of AKI at discharge. BMI above normal weight was not associated with greater eGFR decline per month post-RPN [ 33 ]. Another study by Martini et al showed that in the AKI group there were more patients with increased BMI, 31.3 (26.6, 36.4) vs. 29.0 (25.7, 34.0), p < 0.001.…”
Section: Discussionmentioning
confidence: 99%